2020
DOI: 10.1186/s12888-020-02509-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulating NMDA receptors to treat MK-801-induced schizophrenic cognition deficit: effects of clozapine combining with PQQ treatment and possible mechanisms of action

Abstract: Background: Clozapine has remarkable efficacy on both negative and cognitive symptoms of schizophrenia due to its slight activation of NMDA receptor. In fact, much evidence to the contrary. NMDAR is a complex containing specific binding sites, which are regulated to improve negative symptoms and cognitive deficits associated with individuals affected by schizophrenia. PQQ is a powerful neuroprotectant that specifically binds with NMDA receptors in the brain to produce beneficial physiological and cognitive out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Female animals were included in the MAM model along with the males as there are very few reports on MAM models of schizophrenia using female animals [45,46]. Although the doses of 0.5 mg/Kg and 1.0 mg/Kg of MK-801 were used previously in separate studies, our study involves detailed comparative analysis of behaviour upon administration of these doses [29][30][31][32][47][48][49]. In our treatment regime, the washout period of 5 days ensures that the drug per se won't interfere with the behavior and hence the observed behavioral changes could be arising from the drug-induced changes in the brain tissue (Figure 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female animals were included in the MAM model along with the males as there are very few reports on MAM models of schizophrenia using female animals [45,46]. Although the doses of 0.5 mg/Kg and 1.0 mg/Kg of MK-801 were used previously in separate studies, our study involves detailed comparative analysis of behaviour upon administration of these doses [29][30][31][32][47][48][49]. In our treatment regime, the washout period of 5 days ensures that the drug per se won't interfere with the behavior and hence the observed behavioral changes could be arising from the drug-induced changes in the brain tissue (Figure 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…MK-801 is a non-competitive NMDAR channel blocker. It was intraperitoneally administered in two different doses -0.5 mg/Kg and 1.0 mg/Kg for five days based on previous reports [30][31][32][33]. The resulting blockage of NMDAR is expected to cause alterations in the brain similar to schizophrenia.…”
Section: 41treatment Regimes For the Animal Modelsmentioning
confidence: 99%
“…Chronic ketamine treatment has been previously shown to increase the GluN1/PSD95 and the GluN2A/PSD95 ratio, which is expected to impact calcium signaling ( Lisek et al, 2017 ). In addition, NMDA subunit protein expression increases after chronic MK801 ( Rammes et al, 2001 ; Zhou et al, 2020 ) or PCP ( Yu et al, 2002 ; Anastasio and Johnson, 2004 ) treatments, and this increase has been linked with hyperfunctional NMDA receptors ( Yu et al, 2002 ). On the other hand, studies have also shown inhibitory ( Ding et al, 2016 ; Liu et al, 2018 ; Sun et al, 2021 ) or no effects ( Uttl et al, 2018 ) of these drugs on NMDA subunit expression, possible associated with differences in the dosage regimen.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptor inhibitors such as ketamine and MK-801 are widely used to model schizophrenia in animals. After administration of these compounds, rodents develop cognitive disorders and symptoms resembling positive and negative symptoms of schizophrenia (Mansbach and Geyer 1989;Zhou et al 2020). MK-801, as an NMDA receptor inhibitor, causes a number of changes in the functioning of neurons, including an increase in glutamate release, which may lead to an increase in excitotoxicity, oxidative stress and, consequently, cell death.…”
Section: Highlightsmentioning
confidence: 99%